Edge Detectors as Structural Imaging Tools Using Aeromagnetic Data: A Case Study of Sohag Area, Egypt - Ismael M. Ibraheem; Menna Haggag; Bülent Tezkan (Geosciences, 2019)
The present study was designed to give a clear and comprehensive understanding of the structural situation in the Sohag region and surrounding area by applying several edge detectors to aeromagnetic data. In this research, the International Geomagnetic Reference Field (IGRF) values were removed from the aeromagnetic data and the data obtained were then reduced to the north magnetic pole (RTP). A combination of different edge detectors was applied to determine the boundaries of the magnetic sources. A good correlation was noticed between these techniques, indicating that their integration can contribute to delineating the structural framework of the area. Consequently, a detailed structural map based on the results was constructed. Generally, E-W, N45-60E, and N15-30W directions represent the main tectonic trends in the survey area. The structural map shows the existence of two main basins constituting the most probable places for hydrocarbon accumulation. The results of this study provide structural information that can constitute an invaluable contribution to the gas and oil exploration process in this promising area. They show also that the decision in choosing the location of the drilled boreholes (Balyana-1 and Gerga) was incorrect, as they were drilled in localities within an area of a thin sedimentary cover.